In situ transmission electron microscopy study of the electrochemical sodiation process for a single CuO nanowire electrode. Issue 14 (28th January 2016) - Zhang, Liqiang; Wang, Yuecun; Xie, Degang; Tang, Yushu; Wu, Chunyang; Cui, Lishan; Li, Yongfeng; Ning, Xiaohui; Shan, Zhiwei
Abstract : The electrochemically driven sodiation and desodiation process in a CuO nanowire was characterized by using in situ TEM. This work contributes to understanding of the electrochemical conversion mechanism of CuO nanowire anodes applied in NIBs. Abstract : In this work, an in situ transmission electron microscopy (TEM) study of the electrochemically driven sodiation and desodiation of a CuO nanowire (NW) was performed. Upon sodiation, Na ions first reacted with CuO, yielding a mixture of Cu, Cu2 O, and Na2 O, and then some Cu2 O was subsequently reduced into nanocrystal Cu. The final sodiation product was nanocrystalline Cu mixed with Na2 O and Cu2 O. Upon extraction of Na +, the nanocrystalline Cu first oxidized into Cu2 O and finally transformed back to nanocrystalline CuO. The volume of the CuO NW was found to expand markedly during the first sodiation, but the morphology of the NW remained unchanged during the following cycles. The mechanism by which high-performance CuO NW anodes are used for rechargeable Na ion batteries was analyzed by carrying out an in situ TEM technique based on our results, and this study may be beneficial for designing the optimal structure of the CuO anode, improving its cycle performance, and making CuO more feasible for Na ion batteries.